De novo belatacept in clinical vascularized composite allotransplantation. Issue 7 (9th June 2018) - Cendales, Linda C.; Ruch, David S.; Cardones, Adela R.; Potter, Guy; Dooley, Joshua; Dore, Daniel; Orr, Jonah; Ruskin, Gregory; Song, Mingqing; Chen, Dong‐Feng; Selim, Maria A.; Kirk, Allan D.
Abstract : Most immunosuppressive regimens used in clinical vascularized composite allotransplantation (VCA) have been calcineurin inhibitor (CNI)‐based. As such, most recipients have experienced CNI‐related side effects. Costimulation blockade, specifically CD28/B7 inhibition with belatacept, has emerged as a clinical replacement for CNI‐based immunosuppression in kidney transplantation. We have previously shown that belatacept can be used as a centerpiece immunosuppressant for VCA in nonhuman primates, and subsequently reported successful conversion from a CNI‐based regimen to a belatacept‐based regimen after clinical hand transplantation. We now report on the case of a hand transplant recipient, whom we have successfully treated with a de novo belatacept‐based regimen, transitioned to a CNI–free regimen. This case demonstrates that belatacept can provide sufficient prophylaxis from rejection without chronic CNI‐associated side effects, a particularly important goal in nonlifesaving solid organ transplants such as VCA. Abstract : A hand transplant recipient is successfully treated with a de novo belatacept‐based regimen, then transitioned to a calcineurin inhibitor–free regimen.